Oil and Renewable Energies: A Review - Berry, Ulrich; Levo, Marcelin Phambu; Madimba, John Didrick (Darul Yasin Al Sys, 2025)
Energy plays a critical role in driving the development and sustainability of modern societies, serving as a foundational component in fulfilling essential human needs such as heating, transportation, cooking, and powering industrial and domestic activities. Although renewable energy sources—such as solar, wind, hydro, and biomass—are gaining traction due to their environmental benefits and long-term sustainability, non-renewable sources like oil continue to dominate the global energy system. This study aims to conduct a comparative analysis of renewable energy and oil, examining their respective characteristics, advantages, and limitations. The analysis highlights that while renewable sources are cleaner and replenishable on a human timescale, oil remains a dominant energy source due to its high energy density, ease of storage and transport, and integral role in the global economy. However, the environmental drawbacks and finite nature of oil underscore the urgency of transitioning toward more sustainable alternatives. The findings underscore the necessity of a gradual but deliberate shift toward renewable energy to reduce greenhouse gas emissions, combat climate change, and ensure long-term energy security. This study contributes to the ongoing discourse on sustainable energy transitions and offers insights into the challenges and opportunities associated with reducing global dependence on fossil fuels.